Academic liner notes: a re-inquiry of Chris Hackley's (2012) CCT Blues. Issue 3 (4th May 2018) - Hartmann, Benjamin J.; Ostberg, Jacob
ABSTRACT: While in certain sub-areas of marketing and consumer research, alternative modes of investigation and representation have been mushrooming for a while - i.e. publications of poetry, poetry sessions at conferences, videography, and fiction - we suggest music and complementary academic liner notes as another form of alternative investigation and expression. This paper offers accompanying notes to our original contribution in musical format as an alternative mode of representation and critical dramatization in marketing and consumer research. The song is called CCT Blues and is perfomed by Postmödern talking sans frontiers avéc fromage [the song can be found on Applemusic, iTunes, and Spotify searching for CCT Blues and the artist name.] These liner notes guide the academic listener through our reflexive critical dramatization of the current intellectual condition of the CCT research area in form of a cover song of Chris Hackley's CCT Blues [2012a. CCT Blues Electric Version.wmv, June 2. Accessed November 25, 2016.https://www.youtube.com/watch?v=n1pgyaiw610 ]. Consequently, this paper offers a backstage pass into the world of producing and packaging our critique in audio format.